2016
DOI: 10.3892/ol.2016.4469
|View full text |Cite
|
Sign up to set email alerts
|

Giant elephantiasis neuromatosa in the setting of neurofibromatosis type 1: A case report

Abstract: Abstract. Elephantiasis neuromatosa (EN) can arise from a plexiform neurofibroma of the superficial and deep nerves developing from a hyperproliferation of the perineural connective tissue infiltrating adjacent fat and muscles. To date, the clinical association between EN and neurofibromatosis type 1 (NF1) has been poorly defined, particularly with regard to the role of lymphatic alterations and the consequent lymphedema. The present study reports the clinical and biomolecular features of EN in a NF1 patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…Recently, some authors reported a high incidence of NF1 mutations in DM, suggesting a central role for NF1 in the biology of this MM subtype [17,18]. NF1 is a GTPase-activating protein whose mutations are correlated to neurofibromatosis type 1 [19,20], but also to the development of several neoplasms, such as: glioma, neurofibroma, peripheral nerve sheath tumors, pheochromocytoma, breast cancer and lymphoma [21][22][23].…”
mentioning
confidence: 99%
“…Recently, some authors reported a high incidence of NF1 mutations in DM, suggesting a central role for NF1 in the biology of this MM subtype [17,18]. NF1 is a GTPase-activating protein whose mutations are correlated to neurofibromatosis type 1 [19,20], but also to the development of several neoplasms, such as: glioma, neurofibroma, peripheral nerve sheath tumors, pheochromocytoma, breast cancer and lymphoma [21][22][23].…”
mentioning
confidence: 99%
“…An association between lymphostasis and lymphedema with extensive hyperproliferation of soft tissues in EN has been suggested. 3,4 In the present case, both protection from injuries and continuous compression of the leg might have contributed to improvements in skin condition. We believe the double door–opening system could be optimal for these purposes.…”
Section: Sirmentioning
confidence: 58%
“…This condition is termed elephantiasis neuromatosa (EN). 24 Changes in the vascular and lymphatic system, such as enlarged veins, 2 dilated lymphatics, 3 enlarged lymph nodes, 3,4 and dermal backflow, 4 have been observed in limbs enlarged by EN. Although surgery is the standard treatment for plexiform neurofibroma, 5 conservative treatment might be an option, especially for more complicated cases such as EN.…”
Section: Sirmentioning
confidence: 99%
“…Plexiform neurofibromas affecting a limb (Fig. ) are sometimes described as ‘elephantiasis neuromatosa’ . Moreover, T2SM may involve the brain, eye and orbita, bones and joints, parotis, thyroid, larynx, trachea, lung, heart, oesophagus, upper gastro‐intestinal tract (Fig.…”
Section: Autosomal Dominant Disorders Characterized By Multiple Skin mentioning
confidence: 99%
“…2) are sometimes described as 'elephantiasis neuromatosa'. [34][35][36] Moreover, T2SM may involve the brain, 37 eye and orbita, [38][39][40] bones and joints, [41][42][43][44] parotis, 45 thyroid, 46 larynx, 47 trachea, 48 lung, 49 heart, 41,49,50 oesophagus, 51 upper gastro-intestinal tract ( Fig. 3), 49,52,53 rectum, 54,55 liver, 56,57 gall bladder, 58 pancreas, 56 retroperitoneum 59 and bladder.…”
Section: Introductionmentioning
confidence: 99%